1993
DOI: 10.1002/1097-0142(19930915)72:6<2007::aid-cncr2820720636>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Serum mucin antigens casa and msa in tumors of the breast, ovary, lung, pancreas, bladder, colon, and prostate. A blind trial with 420 patients

Abstract: Background. The tumor markers CASA (cancer‐associated serum antigen) and MSA (mammary serum antigen) have previously been shown to be useful in the clinical management of ovarian and breast carcinoma, respectively, but have not been assessed in other types of cancer. These assays were compared with carcinoem‐bryonic antigen (CEA) and prostate‐specific antigen (PSA) in a blind trial using sera from the Mayo Clinic‐National Cancer Institute (NCI) Diagnostic Serum Bank. Methods. CASA and MSA were assessed retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 14 publications
1
20
0
2
Order By: Relevance
“…For example, PSA also appears in lung and breast tumours [57]. Devine et al [58] compared PSA with other more highly glycosylated antigens as a TAA in colon, breast, prostate, pancreas, lung, bladder and ovary. Changes in the lung have also been correlated with mRNA levels of several MUC genes [59], and the levels of mRNA of a number of other MUC genes have been found increased in different cancer tissues (recently reviewed in [60]).…”
Section: Glycoprotein Antigens In Other Neoplasms and General Clinicamentioning
confidence: 99%
“…For example, PSA also appears in lung and breast tumours [57]. Devine et al [58] compared PSA with other more highly glycosylated antigens as a TAA in colon, breast, prostate, pancreas, lung, bladder and ovary. Changes in the lung have also been correlated with mRNA levels of several MUC genes [59], and the levels of mRNA of a number of other MUC genes have been found increased in different cancer tissues (recently reviewed in [60]).…”
Section: Glycoprotein Antigens In Other Neoplasms and General Clinicamentioning
confidence: 99%
“…Some studies indicate that MUC1 also may play a role in progression and metastasis of prostate cancer, with altered cell-surface expression patterns and aberrant glycosylation. However, the results are variable and often depend on which antibody was used to detect MUC1 [15][16][17][18][19][20]. Gene expression profiling using DNA microarrays has shown that MUC1 correlates with metastasis and disease recurrence in prostate cancer [21].…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that are available suggest that MUC1 also plays a role in progression and metastasis of prostate cancer, usually with higher immunoreactivity, altered cell-surface expression patterns (from apical expression to diffuse staining), and altered glycosylation, although there is still considerable variability among studies. 8,9,[12][13][14][15][16][17] Unfortunately, most of these reports are limited by small sample sizes and are confounded by differences in methodology (eg, antibodies used, processing of tissue samples) and the complexity of the disease itself.…”
Section: Introductionmentioning
confidence: 99%